Khaled Medhat Abou El Fadl’s Thought on Gender - Mahdaniyal H. N. (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
The inequality bared by women is not the spirit of the Qur’an. Their rights for pursuing education, health, and spirituality have been deprived because of many determnations relying on the sacred texts in which Muslims believe as representations of God’s will. Khaled Abou El Fadl criticizes these careless determinations made by jurists. They ignore Qur’anic morality such as equality and justice where there are no distinctions between gender, race, or class. Women are equal to men because they are rewarded and punished in exactly the same way. They have same access to God’s grace and beneficience as men. In accordance with what is recognized as just and fair, women have rights equal to their obligations. Men and women must work together by supporting and helping each other in order to build the moral fabric of society. Keywords: gender, fitnah, Qur’anic morality, jurist